Impact of binet staging versus tumour bulk on treatment outcome in chronic lymphocytic leukaemia - Anazoeze Jude Madu; Helen Chioma Okoye; Ebele Adaobi Muoghalu; Angela Ogechukwu Ugwu; Augustine Nwakuche Duru; Charles Emeka Nonyelu; Ikechukwu Okwudili Anigbogu; Chinedu Anthony Ezekekwu (Nigerian Postgraduate Medical Journal, 2024)
Background: Most of the predictive tools put up to prognosticate treatment outcomes in patients with chronic lymphocytic leukaemia (CLL) are not easily available and affordable in our resource-constrained environment. Aim: The aim of this study was to evaluate the impact of staging and some tumour bulk on treatment outcomes of persons with CLL, Enugu, Nigeria. Patients and Methods: This is a 10-year review of the CLL data from the haemato-oncology unit of a Nigerian tertiary hospital to evaluate the impact of staging and tumour bulk indicators. Data were retrieved from the case notes of 102 patients with CLL receiving care at the facility. Data of interest include basic demographic variables, clinical features including spleen size and disease staging and blood counts. Statistical analysis was done using SPSS version 22. Results: The median absolute lymphocyte count (ALC) was 108.05 (confidence interval [CI] = 50.8–201.3, interquartile range [IQR] = 124.4) ×109/L, and duration of survival for the study cohort was 5.5 (CI = 3.5–31.9, IQR = 27) months. Majority (69, 79.3%) were in Stage C. The Binet stage showed a significant association with the ALC (r = 0.338; P = 0.002) but not with spleen size (r = 0.198; P = 0.056). The duration of survival only showed a significant inverse relationship with the ALC (r = 0.35, P = 0.006) but with neither the Binet stage (r = 0.103, P = 0.431) nor spleen size (r = 0.184, P = 0.116). Conclusion: In CLL patients, ALC at presentation correlates with the duration of survival. We recommend that the ALC at presentation be used as a prognostic marker in our clime.